Obtaining activated carbon from the shells of apricot and peach seeds - Oripova Lobar Norboevna; Hotamov Tolibjon Narzulloevich; Hayitov Ruslan Rustamjonovich (International Journal on Orange Technologies, 2020)
The article presents the results of a study to determine the optimal mode of the process of obtaining activated carbon from the shell of fruit seeds. The conditions of the processes of carbonization and activation of the shell of apricot and peach seeds were studied, determining the bulk density, ash content and adsorption activity of the resulting product for each temperature regime. Based on the obtained experimental results, the corresponding nomograms were compiled.